Hypoglycemic effect of a tablet produced from the atomized extract of Stevia rebaudiana Bertoni in albino rats - Yance, Mercedes (2015)
Stevia rebaudiana Bertoni is an specie with sweetening properties, and a product used as alternative to sugar and artificial sweeteners. The objective of the research was to evaluate the hypoglycemic effect of a tablet made with the atomized extract of leaves of Stevia rebaudiana Bertoni. The hypoglycemic effect was determined using the glucose tolerance test, for which it was used 05 male rats, holtzman strain, average weight 210 ± 10g, divided in 5 groups with 6 specimens each, applying to each group a different treatment. The change in glucose levels versus time were evaluated, the area under the curve (AUC) of the different treatments was calculated. The tablet produced from the atomized stevia extract showed an AUC of 210,68 ± 57, similar to insulin with an AUC of 247,43 ± 24,2. From multiple comparisons of mean AUC, using the Duncan test at 95% confidence level, it was determined that the AUC(s) of insulin therapy, normoglycemic, stevia and glibenclamide are statistically similar (p<,05) although treatment with glyburide is statistically similar to hyperglycemic group (p<0,05). It was concluded that the tablet produced from atomized leaves of Stevia rebaudiana Bertoni extract has hypoglycemic effect.